Model Zebrafish (Danio rerio) Pada Uji Farmakologi dan Toksikologi - Indriyanti, Niken; Wulandari, Sestia; Siregar, Vita Olivia (Journal of Agropharmacy, 2024)
Drug development testing methods continues to result in representative data. The use of rodent experimental animals can still be replaced by using smaller experimental animals, namely zebrafish (Danio rerio). Pharmacological activity test can use zebrafish models that are induced a pathophysiology condition similar to leukemia, melanoma, pancreatic cancer, myocardial infarction, atherosclerosis, diabetes, obesity, Parkinson's disease, Alzheimer's disease, anxiety, muscular dystrophy, osteoporosis, psoriasis, wound, and inflammation. Toxicity tests using zebrafish include acute and chronic toxicity tests, toxicity tests on the heart and liver, and neurotoxic effects. Zebrafish is an ideal model for measuring disease-specific biomarkers and toxicity biomarkers in humans.